Battle for Metals: Regulatory RNAs at the Front Line - Charbonnier, Mathilde; González-Espinoza, Gabriela; Kehl-Fie, Thomas E.; Lalaouna, David (Frontiers in Cellular and Infection Microbiology, 2022)
Metal such as iron, zinc, manganese, and nickel are essential elements for bacteria. These nutrients are required in crucial structural and catalytic roles in biological processes, including precursor biosynthesis, DNA replication, transcription, respiration, and oxidative stress responses. While essential, in excess these nutrients can also be toxic. The immune system leverages both of these facets, to limit bacterial proliferation and combat invaders. Metal binding immune proteins reduce the bioavailability of metals at the infection sites starving intruders, while immune cells intoxicate pathogens by providing metals in excess leading to enzyme mismetallation and/or reactive oxygen species generation. In this dynamic metal environment, maintaining metal homeostasis is a critical process that must be precisely coordinated. To achieve this, bacteria utilize diverse metal uptake and efflux systems controlled by metalloregulatory proteins. Recently, small regulatory RNAs (sRNAs) have been revealed to be critical post-transcriptional regulators, working in conjunction with transcription factors to promote rapid adaptation and to fine-tune bacterial adaptation to metal abundance. In this mini review, we discuss the expanding role for sRNAs in iron homeostasis, but also in orchestrating adaptation to the availability of other metals like manganese and nickel. Furthermore, we describe the sRNA-mediated interdependency between metal homeostasis and oxidative stress responses, and how regulatory networks controlled by sRNAs contribute to survival and virulence.